Cell division cycle 7 kinase is a negative regulator of cell-mediated collagen degradation. - Podolsky, M.J.; Gupta, D.; Ha, A.; Ta, R.; Khalifeh-Soltani, A.; McKleroy, W.; Datta, R.; Sheppard, D.; Atabai, K. (American journal of physiology. Lung cellular and molecular physiology, 2018)
Although extensive work has delineated many of the mechanisms of extracellular matrix (ECM) production, far less is known about pathways that regulate ECM degradation. This is particularly true of cellular internalization and degradation of matrix, which play an underappreciated role in ECM metabolism and lung fibrosis. For example, genetic perturbation of this pathway leads to exacerbated fibrosis in experimental animal models. In this work, we present the results of an unbiased screen of Drosophila phagocytes that yielded multiple genes that, when silenced, led to increased collagen uptake. We further describe the function of cell division cycle 7 kinase (CDC7) as a specific suppressor of collagen uptake. We show that the genetic or pharmacological inhibition of CDC7 results in increased expression of the collagen endocytic receptor Endo180. Chromobox 5 (CBX5) is a putative target of CDC7, and genetic silencing of CBX5 also results in increased Endo180 and collagen uptake. Finally, CRISPR-mediated activation of Endo180 expression results in increased collagen uptake, suggesting that CDC7 regulates collagen internalization through increased Endo180 expression. Targeting the regulatory elements of the collagen degradative machinery may be a useful therapeutic approach in diseases of fibrosis or malignancy.